Community Service: Development of Indonesian Traditional Games for Early Childhood Education for Teachers in Germany and Indonesia - Pujiastuti, Sri Indah; Apriliani, Nadia; Nisrina, Dhiya Nada; Lusyana, Lusyana; Putri, Nurhalizha Amalia; Kaiser, Astrid (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to introduce and develop traditional Indonesian games for early childhood to kindergarten teachers in Germany and Indonesia. The games developed include Dhakon, Genteuk Bruek, Bakiak, Cenge-Cenge, and Kotak Karet. Through this program, teachers are trained on how to adapt traditional Indonesian games to the context of early childhood education, as well as how to utilize these games to support children's cognitive, motor, social, and emotional development. The activities are conducted using lectures, Q&A sessions, and hands-on practices involving teachers from both countries. In addition to enriching pedagogical approaches, this program also contributes to the preservation of local culture amidst globalization. The data produced in this community service program is derived from a comprehensive evaluation of the impact of traditional Indonesian games on early childhood education in Germany and Indonesia. The primary data sources include pre-test and post-test scores, observational data, and feedback collected through questionnaires and interviews. The pre-test and post-test scores provide quantitative evidence of the improvement in teachers' understanding of the educational value of traditional games. Observational data captures the engagement and active participation of teachers during workshops, while qualitative feedback from questionnaires and interviews highlights the perceived benefits and challenges of integrating traditional games into early childhood curricula. This data underscores the effectiveness of traditional games in enhancing cognitive, motor, social, and emotional development in young children, as well as promoting cross-cultural understanding and cultural preservation. This program not only fosters cross-cultural understanding but also encourages the use of creative, local wisdom-based teaching methods.